'Fit for Purpose in Today's Society?': Reflecting on Provocation Pleas in Modern Scotland. (April 2023) - McPherson, Rachel
Provocation has been the subject of long-term, international scrutiny and is currently under consideration by the Scottish Law Commission as part of their review of homicide and defences to murder. This article reflects on how provocation is used in practice in Scottish courts and considers two aspects of potential reform in particular: where the basis of the plea is infidelity and where the plea is used in the context of someone killing an abuser. It is recognised that reform of the plea now appears inevitable (and required) but this article cautions against complete abolition or expansion of the plea. The discussion is informed by critical feminist analysis of both reported and unreported cases and seeks to better illuminate how the plea is currently operating in practice.